Особливості технології виведення доменних печей із експлуатації - Крячко, Г.Ю.; Сігарьов, Є.М. (Physico-technological Institute of Metals and Alloys, 2025)
The aim of the work is to improve the technology of safe blowing of blast furnaces by substantiating the choice of the volume of idle coke and the dynamics of changes in the gas-blowing mode of the blowing process. To determine the directions of improving the technology of the blowing process, we considered the characteristic modes and formulated the tasks of these modes in accordance with the analyzed information. Consideration of the tasks that certain modes of the blowing process must solve shows that the modes of forming the charge column and the gas-blowing parameters, the study of which was focused on, are decisive in creating conditions for safe blowing of furnaces. It is shown that to determine the justified volume of idle coke, the taper of the top of the coke nozzle should be taken into account, which increases with the increase in the volume of blast furnaces. It is proposed to estimate the taper of the top of the nozzle by the ratio of the shoulder volume Vs to the furnace diameter df. It is established, firstly, that the value of the ratio Vs/df is satisfactorily correlated with the volume of idle coke from the practice of PJSC "ArcelorMittal Kryvyi Rih". Secondly, a higher level of filling the shoulders with idle coke of a powerful furnace eliminates to a certain extent the breakthrough of tuyeres gases through its layer. The feasibility of considering the gas dynamics of the blowing process as a single systemic whole with simultaneous consideration of the characteristics of the charge column, the parameters of the blast and the gas in the furnace space is shown. The leading role of increased gas pressure in establishing a safe gas-blasting mode of the blowing process is shown on examples of decommissioning industrial blast furnaces. To ensure safe blowing of the blast furnace, the resistance of the charge column to the gas flow ∆Р at the beginning of the blowing process can be equal to the excess pressure of gases on the top Pk or exceed it ∆Р ≥ Pk. In the process of reducing the height of the blowing charge column, the inverse inequality Pk > ∆Р should be maintained, which eliminates the possibility of tuyeres gas breakthrough through the charge column. The results obtained by the authors allow improving the technology of safe blowing of blast furnaces.